2009
DOI: 10.2174/187221309789257360
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone in Therapy of Allergic Diseases

Abstract: Dehydroepiandrosterone (DHEA) and its sulfate derivative (DHEA-S) are weak androgens produced in the adrenals and serve as primary precursors in biosynthesis of both, androgens and estrogens. These hormones are proposed to perform immunoenhancing activities and may play a crucial role in regulating cytokine production by Th1/Th2 cells; however, their role in immune-mediated diseases is controversial. The primary physiological role of DHEA-(S) and its mechanism is unclear. This review is a brief summary of rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Zenon Brzoza et al in their study showed that the decline in dehydroepiandrosterone sulfate observed in CU is associated with psychological distress. [ 23 ] Depression may also cause or aggravate CU. [ 24 ]…”
Section: Etiologymentioning
confidence: 99%
“…Zenon Brzoza et al in their study showed that the decline in dehydroepiandrosterone sulfate observed in CU is associated with psychological distress. [ 23 ] Depression may also cause or aggravate CU. [ 24 ]…”
Section: Etiologymentioning
confidence: 99%
“…So far only some of the studies have evaluated the effectiveness of DHEA in the treatment of bronchial asthma. The patent-based research carried out points to DHEA-S capable of reducing asthmatic symptoms in patients with a history of exercise-induced asthma [for review [39]]. …”
Section: Dhea In the Therapy Of Asthmamentioning
confidence: 99%
“…A membrane bound receptor was identified in endothelial cells, heart, liver and kidney which reacts with DHEA specifically with high affinity and can lead to stimulation of endothelial nitric synthase (eNOS) expression as well as activity (Liu and Dillon, 2002). This can further lead to downstream effects including stimulating endothelial proliferation, increasing flow-mediated dilation (Williams et al, 2004), reducing adhesion of monocytes to endothelial cells, amelioration inflammatory responses, and the production of ROS (Kasperska-Zajac et al, 2009;Curatola et al, 2012). Clinical studies have revealed a protective effect of DHEA against cardiovascular diseases including ischemic heart disease and congestive heart failure (Beer et al, 1996;Feldman et al, 2001;Shufelt et al, 2010).…”
Section: Endogenous Compound Metabolism and Physiological Impactmentioning
confidence: 99%